1999
DOI: 10.2337/diabetes.48.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute ketosis on the endothelial function of type 1 diabetic patients: the role of nitric oxide.

Abstract: In type 1 diabetic patients, acute loss of metabolic control is associated with increased blood flow, which is believed to favor the development of long-term complications. The mechanisms for inappropriate vasodilation are partially understood, but a role of endothelium-derived nitric oxide (NO) production can be postulated. We assessed, in type 1 diabetic patients, the effect of the acute loss of metabolic control and its restoration on forearm endothelial function in 13 type 1 diabetic patients who were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…This experimental model differs from clinical ketoacidosis in the relatively limited rises in glucagon and catecholamine levels as observed in our previous studies [2,10]. Thus caution must be adopted in extrapolating the present findings into a clinical setting.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This experimental model differs from clinical ketoacidosis in the relatively limited rises in glucagon and catecholamine levels as observed in our previous studies [2,10]. Thus caution must be adopted in extrapolating the present findings into a clinical setting.…”
Section: Discussionmentioning
confidence: 64%
“…At the second appointment, scheduled 7 days later, the patient was admitted to the Metabolic Unit at 6.00 p.m. Before supper, two‐thirds of their usual dose of soluble insulin and no intermediate or long‐acting insulin were given. This was done to induce mild ketosis by the following morning [2,10]. No patient reported hypoglycaemic episodes the day before.…”
Section: Methodsmentioning
confidence: 99%
“…Under these circumstances, total ketone bodies may exceed 10 mmol/l, while those of normal subjects are less than 0.5 mmol/l [13]. Ketoacidosis is a major complication of Type I diabetes, and also enhances endogenous AGE formation by stimulating nitric oxide (NO) release from vascular endothelial cells [14], oxygen radical formation and lipid peroxidation [15]. Diabetic patients with frequent episodes of ketoacidosis suffer from increased incidences of vascular diseases, morbidity and mortality [16].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies demonstrated that the activity of eNOS and generation of nitric oxide (NO) are significantly reduced in endothelial cells exposed to a hyperglycemic environment [7, 9, 23, 41]. It has been demonstrated that mouse microvascular endothelial cells (MMECs) develop oxidative stress after exposure to high glucose [42].…”
Section: Molecular Basis Of Endothelial Dysfunction In Diabetes—cumentioning
confidence: 99%